Living well with bipolar disorder a new look - Guilford Publications, Inc. (New York : Guilford Publications, 2002)
(Producer) Six individuals describe the impact bipolar disorder has had on their lives and the strategies they have learned for dealing with it. Provides discussion of the elements of effective clinical management. Shows how individuals can stay well by combining medication, counseling or psychotherapy, attention to early warning signs of relapse, and sensible lifestyle choices
Keywords: Bipolar Disorder -- personal narratives; Bipolar Disorder -- therapy -- personal narratives